Situation Report: Romania, 14 September 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Increased African Contacts Romanian-Kampuchean Relations New Endeavors in Middle East Diplomacy The UN Conference on Science and Technology Romania Searchers for New Energy Sources